Development and Validation of HPTLC Method for Simultaneous Estimation of Diosgenin and Quercetin in Fenugreek Seeds (Trigonella foenum-graceum). (10th April 2014) - Laila, Omi; Murtaza, Imtiyaz; Abdin, M. Z.; Ahmad, S.; Ganai, Nisar Ahmad; Jehangir, Majid
Abstract : A sensitive, fast, and reproducible high performance thin-layer chromatographic method has been developed for simultaneous analysis of diosgenin and quercetin from fenugreek seeds, using TLC aluminium plates precoated with silica gel G60F254. Among the different combinations of mobile phases used, best separation was achieved in Toluene-ethyl acetate-formic acid (5 : 4 : 1, v / v / v ). Densitometric scanning of the plates directly at 275nm was used for analysis of quercetin. While as for analysis of diosgenin, plates were scanned at 450nm after spraying with anisaldehyde-sulphuric acid reagent. The retardation factorvalue of diosgenin and quercetin was found to be 0.69 ± 0.02 and 0.57 ± 0.02, respectively. The method was validated for specificity, precision (intraday and interday), accuracy, and robustness. Accuracy of the method was checked by recovery study of three different levels with the average percentage recovery of 99.13 ± 0.26 for diosgenin and 99.63 ± 0.34 for quercetin, respectively. Dried fenugreek seed samples were found to contain diosgenin in the range of 0.113–0.135% (w/w) and quercetin in the range of 0.009–0.012% (w/w). The present method is being reported for the first time and can be used for routine quality control and quantification of these marker compounds in various plant samples, extracts, and market formulations.